2014
DOI: 10.1089/ars.2013.5615
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Store-Operated Ca2+Entry

Abstract: Significance: Store-operated Ca 2+ entry (SOCE) is a ubiquitous Ca 2+ signaling mechanism triggered by Ca 2+ depletion of the endoplasmic reticulum (ER) and by a variety of cellular stresses. Reactive oxygen species (ROS) are often concomitantly produced in response to these stresses, however, the relationship between redox signaling and SOCE is not completely understood. Various cardiovascular, neurological, and immune diseases are associated with alterations in both Ca 2+ signaling and ROS production, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 219 publications
0
44
0
Order By: Relevance
“…But, whether ginsenoside Rb1 acts directly through interactions with STIM1, TRPC1 and Orai1, or indirectly through other signaling pathways is unclear. Recent evidence has indicated that SOCE can be regulated by reactive oxygen species (ROS) through redox-dependent modification of STIM and Orai proteins [57]. Since ginsenoside Rb1 is known to reduce oxidative stress in different cells and tissues [17,27,58,59], it is possible that it modulates SOCE through a ROS-related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…But, whether ginsenoside Rb1 acts directly through interactions with STIM1, TRPC1 and Orai1, or indirectly through other signaling pathways is unclear. Recent evidence has indicated that SOCE can be regulated by reactive oxygen species (ROS) through redox-dependent modification of STIM and Orai proteins [57]. Since ginsenoside Rb1 is known to reduce oxidative stress in different cells and tissues [17,27,58,59], it is possible that it modulates SOCE through a ROS-related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For more details regarding redox regulation of ion channels in different immune and non-immune cell types we recommend the following literature: Bogeski et al (2011);Takahashi et al (2011);Bogeski and Niemeyer (2014); O-Uchi et al (2014a, b); Kozai et al (2014); Nunes and Demaurex (2014); Paula-Lima et al (2014); Sahoo et al (2014); Stojilkovic et al (2014); Todorovic and Jevtovic-Todorovic (2014).…”
Section: What Are the Targets Of Ros?mentioning
confidence: 99%
“…There would also likely be an accompaniment of activation on TRPV 1 , a redox sensor responding to increased ROS 196 and store-operated Ca 2+ entry. 197 This mechanism is important in the acute synovial inflammation that results in TRPV 1 -mediated cell destruction 198 and points to a role of PrP C in modulating inflammatory joint disease. PrP C and body symmetry.…”
Section: Signal Transduction Insights 2014:3mentioning
confidence: 98%